Weakly Non-Linear Shape Oscillations of Inviscid Drops - Brenn, Günter (Graz University of Technology, 2021)
References:
D. Zrnić, G. Brenn: Weakly Non-Linear Shape Oscillations of Inviscid Drops. J. Fluid Mech. vol. 923, A9 (2021), https://doi:10.1017/jfm.2021.568
D. Zrnić, G. Brenn: Weakly Non-Linear Shape Oscillations of Inviscid Drops - Supplement. J. Fluid Mech. vol. 923, A9 (2021), https://doi.org/10.1017/jfm.2021.568
Journal of Fluid Mechanics is published by Cambridge University Press.